REAÇÃO DE CAFEEIROS A Meloidogyne javanica - Oliveira, Cláudio Marcelo Gonçalves de; Kubo, Roberto Kazuhiro; Antedomênico, Sônia Regina; Monteiro, Ailton Rocha (REVISTA DE AGRICULTURA, 2015)
REAÇÃO DE CAFEEIROS A Meloidogyne javanica